Prolactin secretion in healthy adults is determined by gender, age and body mass index. - Ferdinand Roelfsema (Public Library of Science (PLoS), 2012)
Background Prolactin (PRL) secretion is quantifiable as mean, peak and nadir PRL concentrations, degree of irregularity (ApEn, approximate entropy) and spikiness (brief staccato-like fluctuations). Hypothesis Distinct PRL dynamics reflect relatively distinct (combinations of) subject variables, such as gender, age, and BMI. Location Clinical Research Unit. Subjects Seventy-four healthy adults aged 22-77 yr (41 women and 33 men), with BMI 18.3-39.4 kg/m(2). Measures Immunofluorometric PRL assay of 10-min samples collected for 24 hours. Results Mean 24-h PRL concentration correlated jointly with gender (P<0.0001) and BMI (P = 0.01), but not with age (overall R(2) = 0.308, P<0.0001). Nadir PRL concentration correlated with gender only (P = 0.017) and peak PRL with gender (P<0.001) and negatively with age (P<0.003), overall R(2) = 0.325, P<0.0001. Forward-selection multivariate regression of PRL deconvolution results demonstrated that basal (nonpulsatile) PRL secretion tended to be associated with BMI (R(2) = 0.058, P = 0.03), pulsatile secretion with gender (R(2) = 0.152, P = 0.003), and total secretion with gender and BMI (R(2) = 0.204, P<0.0001). Pulse mass was associated with gender (P = 0.001) and with a negative tendency to age (P = 0.038). In male subjects older than 50 yr (but not in women) approximate entropy was increased (0.942±0.301 vs. 1.258±0.267, P = 0.007) compared with younger men, as well as spikiness (0.363±0.122 vs. 0463±2.12, P = 0.031). Cosinor analysis disclosed higher mesor and amplitude in females than in men, but the acrophase was gender-independent. The acrophase was determined by age and BMI (R(2) = 0.186, P = 0.001). Conclusion In healthy adults, selective combinations of gender, age, and BMI specify distinct PRL dynamics, thus requiring balanced representation of these variables in comparative PRL studies.